Successful treatment of intractable menstrual migraine with the traditional herbal medicine tokishakuyakusan. (3rd April 2019) - Akaishi, Tetsuya; Takayama, Shin; Ohsawa, Minoru; Kikuchi, Akiko; Arita, Ryutaro; Nakashima, Ichiro; Aoki, Masashi; Ishii, Tadashi
Abstract: In this report, we present the successful treatment of five consecutive cases of premenopausal women suffering from severe menstrual migraine with tokishakuyakusan (TSS). Two patients were complicated by tension‐type headache (TTH), and another patient was by medication overuse headache (MOH). The effects of triptans were limited in all of them. After starting TSS, they showed dramatic improvement in the severity and frequency of their attacks. The patients with TTH and MOH also showed dramatic improvement in their symptoms. TSS could be a promising alternative choice for patients with intractable menstruation–related headaches that are refractory to conventional treatments, including triptans. Abstract : We present successful treatments of five consecutive cases of premenopausal women suffering from severe triptan‐refractory menstrual migraine with tokishakuyakusan (TSS). After starting TSS, they showed dramatic improvement in the severity and frequency of their attacks and the frequency of taking anti‐headache drugs also decreased. TSS could be a promising choice as an alternative medication for patients with intractable menstruation–related headaches that are refractory to conventional treatments.